Adoption of Children in the Perspective of National Law and its Relation to Religious Courts - Rachman Hakim, Arief; Rachman Hakim, Arief (KnE Social Sciences, 2024)
The constellation of child adoption from the perspective of national law in Indonesia has received serious attention, but there is still a weak point, namely the absence of legal unity regarding child adoption. The adoption of children is one of the authorities of the Religious Court. The competence of religious courts is affirmed in Article 49 of Law Number 3 of 2006 concerning Amendments to Law Number 7 of 1989 concerning Religious Courts. The procedures and requirements for submitting applications for child adoption have been regulated in detail and concretely in various child adoption regulations, including Government Regulation Number 54 of 2007 challenging the Implementation of Child Adoption. There should be legal unity, namely a law-level regulation governing the adoption of Indonesian children. The government should socialize the strengthening of the position and authority of religious courts in the adoption of children for Muslims. Socialization is needed so that the purpose of laws and regulations governing the norms of the adoption of children for Muslims is in accordance and in line with the objectives of applicable law. Muslims who wish to adopt children should be carried out in religious courts as absolute and representative authority for the practice of Islamic law. Keywords: adoption of children, national law, religious cou